Could Camrelizumab Plus Chemotherapy Improve Clinical Outcomes in Advanced Malignancy? A Systematic Review and Network Meta-Analysis - Yang, Chao; Xu, Chang; Li, Xiang; Zhang, Yaowen; Zhang, Simeng; Zhang, Tongyu; Zhang, Yingshi (Frontiers in Oncology, 2021)
Purpose: Camrelizumab is a novel programmed cell death 1 (PD-1) inhibitor. To determine the efficacy and safety of the combination treatment of camrelizumab+chemotherapy and camrelizumab monotherapy, and determine which is the most suitable malignancy type to be treated with camrelizumab, we performed a systematic review and network meta-analysis. Methods: We searched PubMed, Embase, and the Cochrane Library for published clinical trials from database inception until April 2021. Studies that compared camrelizumab+chemotherapy and camrelizumab monotherapy in patients with advanced malignancy were included. We estimated odds ratios (ORs) with credible intervals (CIs) using network meta-analysis with random effects. Results: We included four clinical trials with 946 advanced malignancy patients. In terms of the efficacy evaluation of the objective response rate and progression-free survival, camrelizumab treatment for Hodgkin lymphoma (HL), camrelizumab treatment for oesophageal squamous cell carcinoma (OSCC), and camrelizumab+chemo treatment for HL always ranked first. In terms of safety evaluation from leukocytopenia, hypothyroidism and asthenia, camrelizumab treatment for OSCC and chemo always ranked first. This study was registered with PROSPERO, number CRD42021249193. Conclusions: Patients with advanced OSCC should be treated with camrelizumab. Patients with severely relapsed/refractory HL could use camrelizuma+chemo for combination treatment when they can tolerate adverse reactions.